2019
DOI: 10.1590/0100-29452019154
|View full text |Cite
|
Sign up to set email alerts
|

Initial growth and physiological indexes of Fig accessions in active germoplasm bank

Abstract: Fruit growing has become an important alternative economic strategy for the social reproduction of small rural producers. Fig (Ficus carica L.) is a fruit of great world importance, and can be used as a new source of agricultural variability, adding advantages, both economically and socially. In addition, the characterization of active germplasm banks of the genus Ficus becomes an important research line for culture improvement, and it is necessary to gather information, mainly in relation to its genetic varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
(21 reference statements)
0
3
0
2
Order By: Relevance
“…Dalastra et al (2009) reported that four-yearold plants pruned in August showed a mean branch length of 128.43 cm at the end of the cycle. In turn, Rodrigues et al (2019a) evaluated one-year-old plants, and found higher lengths for 'Roxo de Valinhos' (101 cm), Troyano (100 cm), and White Genova (93 cm) than PI-189 (71 cm). These differences can be attributed to climatic and cultivation conditions during plant growth, as well as to genetic factors and plant age.…”
Section: Resultsmentioning
confidence: 99%
“…Dalastra et al (2009) reported that four-yearold plants pruned in August showed a mean branch length of 128.43 cm at the end of the cycle. In turn, Rodrigues et al (2019a) evaluated one-year-old plants, and found higher lengths for 'Roxo de Valinhos' (101 cm), Troyano (100 cm), and White Genova (93 cm) than PI-189 (71 cm). These differences can be attributed to climatic and cultivation conditions during plant growth, as well as to genetic factors and plant age.…”
Section: Resultsmentioning
confidence: 99%
“…The great vegetative vigor observed in 'Troyano' and 'White Genova' emphasizes the need for continuous follow up examinations of these cultivars at different planting densities. Rodrigues et al (2019a) considered moderated vegetative growth in 'Roxo de Valinhos', 'White Genova' and 'Troyano', while 'Troyano' (Figure 2B). According to Cantuaria-Avilés, Mourão, Stuchi, Silva and Nunez (2010), there is a negative correlation to some extent between productive efficiency and canopy volume.…”
Section: Canopy Volume and Productive Efficiencymentioning
confidence: 99%
“…Growth analyses are used to explain differences in plant growth due to genetic or environmental changes (Rodrigues et al, 2019) and can be associated with physiological indices to identify morphophysiological conditions influenced by biotic and abiotic factors (Fontes et al, 2005). Multivariate statistical analyses are important for understanding the genetic relationships between morphophysiological characteristics and genetic materials and the variability of germplasm collections.…”
Section: Introductionmentioning
confidence: 99%